MINERAGENY OF THE UFALEI BLOCK (MIDDLE URALS) IN CONNECTION WITH LITHOTECTONIC COMPLEXES OF DIFFERENT GEODYNAMIC SETTINGS - Ogorodnikov V.N.; Sazonov V.N.; Polenov Y.A. (My University, 2007)
The relatively well-studied Ufalei Block represents a key structure for understanding the genesis and economic potential of other similar blocks: Sysert, Il’menogorsk–Vishnevogorsk, Marunkeu, and others. The available geological and radiological data and original materials show that the Ufalei gneiss–amphibolite complex underwent several stages of structural–tectonic and metamorphic transformation, each accompanied by the formation of particular igneous complexes, which produced carbonatites, pegmatites, different metasomatites, vein quartz, and other rocks during the postmagmatic stage
Keywords: Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей